Zn(OTf)2-Mediated Expeditious and Solvent-Free Synthesis of Propargylamines via C–H Activation of Phenylacetylene - Sarode, Prashant B; Bahekar, Sandeep P; Chandak, Hemant S (Synlett, 2016)
Zn(OTf)2-mediated expeditious and solvent-free synthesis of propargylamines via A3 coupling of aldehydes, amines, and phenylacetylene has been described. The described protocol proceeds effectively with variety of substituted benzaldehydes, enolizable aldehyde, and formaldehyde. Recyclability of the catalyst, low catalyst loading, and use of inexpensive catalyst are the key features of the present protocol.
Keywords: Zn(OTf)2; solvent-free synthesis; C–H activation; A3 coupling; propargylamine